2018
DOI: 10.1016/j.janxdis.2018.05.007
|View full text |Cite|
|
Sign up to set email alerts
|

A network analysis of DSM-5 posttraumatic stress disorder and functional impairment in UK treatment-seeking veterans

Abstract: Network analysis is a relatively new methodology for studying psychological disorders. It focuses on the associations between individual symptoms which are hypothesized to mutually interact with each other. The current study represents the first network analysis conducted with treatment-seeking military veterans in UK. The study aimed to examine the network structure of posttraumatic stress disorder (PTSD) symptoms and four domains of functional impairment by identifying the most central (i.e., important) symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
58
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 67 publications
3
58
0
1
Order By: Relevance
“…Psychological Medicine Spiller et al, 2017;Afzali et al, 2017a;McNally et al, 2017a;Greene et al, 2018;Ross et al, 2018;Vanzhula et al, 2018). For adequate power, sample size should be considerably larger than the number of parameters estimated in analyses, which given the number of variables in PTSD-related networks, tends to be relatively high (Spiller et al, 2017;Afzali et al, 2017aAfzali et al, , 2017bMcNally et al, 2017a, Fried et al, 2018) 1 † .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Psychological Medicine Spiller et al, 2017;Afzali et al, 2017a;McNally et al, 2017a;Greene et al, 2018;Ross et al, 2018;Vanzhula et al, 2018). For adequate power, sample size should be considerably larger than the number of parameters estimated in analyses, which given the number of variables in PTSD-related networks, tends to be relatively high (Spiller et al, 2017;Afzali et al, 2017aAfzali et al, , 2017bMcNally et al, 2017a, Fried et al, 2018) 1 † .…”
mentioning
confidence: 99%
“…For example, while amnesia is found to be the least central symptom in most PTSD network studies (McNally et al ., 2015, Armour et al ., 2017, Birkeland and Heir, 2017, Bryant et al ., 2017, Mitchell et al ., 2017, Spiller et al ., 2017, Afzali et al ., 2017 a , McNally et al ., 2017 a , Benfer et al ., 2018, Fried et al ., 2018, Moshier et al ., 2018, Papini et al ., 2018, Phillips et al ., 2018, Ross et al ., 2018, Vanzhula et al ., 2018, von Stockert et al ., 2018), symptoms emerging as most central vary considerably across studies, including, among others, getting emotionally upset due to trauma reminders, hypervigilance, intrusive thoughts, concentration difficulties, nightmares, future foreshortening, negative trauma related emotions, detachment, loss of interest, emotional numbing, physical reactions to trauma reminders, and flashbacks (Phillips et al ., 2018). Recently, it has been suggested that these mixed findings might be the result of corresponding differences in traumatic events, such as, for example, man-made trauma v. natural disasters, as this has been shown to affect PTSD presentation, and hence, network structure (Ross et al ., 2018; Sullivan et al ., 2018). Interestingly, when limiting past research to include only veteran samples, a more consistent result pattern emerges, demonstrating high centrality of getting emotionally upset by trauma reminders (Armour et al ., 2017; Mitchell et al ., 2017; Fried et al ., 2018; Moshier et al ., 2018; von Stockert et al ., 2018).…”
mentioning
confidence: 99%
“…These symptoms appear similar to the DSM-5 PTSD symptoms of 'detachment' and 'diminished interest' that have previously been shown to be associated with greater levels of functional impairment in veterans with PTSD. 26 Again, this could imply the need to specifically target these symptoms during treatment. It is also important to acknowledge that the ITQ may not be able to differentiate between CPTSD and personality disorder and that future research should aim to explore this further.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that due to methodological consideration, such as cross-sectional designs, various types of trauma, time since exposure, full diagnosis vs., sub-syndrome and so on-it seems that stability within PTSD clusters, but high lack of consistency of between-clusters connectivity of network model (e.g. Ross, Murphy, & Armour, 2018) is the norm.…”
Section: Introductionmentioning
confidence: 99%